Prevalence and exposure levels to psychosocial factors and risks through ISTAS-21 - Esmeralda MONTALVO SÁNCHEZ; Eloísa GUERRERO BARONA; Marta RODRÍGUEZ JIMÉNEZ; Jonás AGUDO OSUNA; Juan Manuel MORENO MANSO; Daniel PAREDES GÓMEZ (Siglo Cero, 2020)
The main purpose of the present study is to evaluate and to explain the presence of psychosocial risks in a cross-section of staff working with people with intellectual disabilities from Extremadura (Spain). With this aim, Istas-21 instrument has been used. The cross-section was composed of 518 workers of different entities, 169 are men (30,11 %) and 349 are women (67,37 %). Three psychosocial constructs of Istas-21 have been analyzed: psychosocial demands, double presence and time management, considering different variables (age, sex, department, numbers of years spent on the work, job position and type of contract). These constructs include ten dimensions of the questionnaire which have been deeply evaluated. The results indicate that participants are more affected by the dimensions of the demands of hiding emotions, double presence and time management at work.